Co-distribution pattern of a haemogregarine Hemolivia mauritanica (Apicomplexa: Haemogregarinidae) and its vector Hyalomma aegyptium (Metastigmata: Ixodidae) - Siroký, Pavel; Mikulícek, Peter; Jandzík, David; Kami, Hajigholi; Mihalca, Andrei D; Rouag, Rachid; Kamler, Martin; Schneider, Christoph; Záruba, Martin; Modrý, David (The Journal of parasitology, 2009)
Hyalomma aegyptium ticks were collected from tortoises, Testudo graeca, at localities in northern Africa, the Balkans, and the Near and Middle East. The intensity of infestation ranged from 1-37 ticks per tortoise. The sex ratio of feeding ticks was male-biased in all tested populations. Larger tortoises carried more ticks than did the smaller tortoises. The juveniles were either not infested, or carried only a poor tick load. Hyalomma aegyptium was absent in the western Souss Valley and Ourika Valley in Morocco, the Cyrenaica Peninsula in Libya, Jordan, and the Antilebanon Mountains in Syria. Hemolivia mauritanica, a heteroxenous apicomplexan cycling between T. graeca and H. aegyptium, was confirmed in Algeria, Romania, Turkey, Syria, Lebanon, and Iran. Its prevalence ranged from 84% in Romania (n = 45), 82% in eastern Turkey (n = 28), and 82% in the area of northwestern Syria with adjacent Turkish borderland (n = 90), to 38% in Lebanon (n = 8) and in only 1 of 16 sampled tortoises in Algeria. The intensity of parasitemia in the studied areas ranged from 0.01% up to 28.17%. The percentage of Hemolivia-infected erythrocytes was significantly higher in adults. All tortoises from Hyalomma-free areas were Hemolivia-negative. Remarkably, all 29 T. graeca from Jabal Duruz (southwestern Syria) and 36 T. graeca from the area north of Middle Atlas (Morocco) were Hemolivia-negative, despite the fact that ticks parasitized all adult tortoises in these localities. Identical host preferences of H. aegyptium and H. mauritanica suggest the occurrence of co-evolution within the Testudo-Hyalomma-Hemolivia host-parasite complex.
Keywords: Analysis of Variance; Animals; Rumunsko; Romania; želvy; Female; Prevalence; arachnida jako vektory; Middle East; infestace klíšťaty; ženské pohlaví; Protozoan Infections, Animal; Střední východ; Host-Parasite Interactions; Sex Ratio; interakce hostitele a parazita; Africa, Northern; Ixodidae; prevalence; analýza rozptylu; Male; poměr pohlaví; protozoální infekce zvířat; Apicomplexa; Turtles; zvířata; mužské pohlaví; Arachnid Vectors; severní Afrika; Tick Infestations